MEKANISME HAWALAH DENGAN DANA INFAK DALAM PEMBIAYAAN USAHA SYARI’AH KOTA MOJOKERTO - Muh. Hasbi Ash. Shiddiq (Fakultas Ekonomi dan Bisnis Islam IAIN Bone, 2021)
This article aims to find out the debt transfer agreement in the PUSYAR program. PUSYAR is a program to strengthen UMKM where PUSYAR participants get business capital assistance with a murabahah scheme. The margin from the murabahah is paid by the Mojokerto City Baznas using infaq funds. This research is descriptive qualitative with a case study approach to find out the phenomenon and find the meaning of a case. The results of this study are, the contract in the process flow of the transfer of margin debt from the murabahah contract is in the form of a hawalah contract where BAZNAS (muhal 'alaih) pays the margin debt of PUSYAR participants ( muhil) to the BPRS (muhal).